Hearing preservation after cochlear implantation evaluated using Auditory Steady State Responses - Haumann, Sabine; Büchner, Andreas; Lenarz, Thomas; Salcher, Rolf B. (Frontiers in Audiology and Otology, 2025)
IntroductionFor several years now, also patients with significant acoustic hearing can receive a cochlear implant in order to combine acoustic and electric hearing. For this purpose, atraumatic electrodes were designed and used as standard. Tools were developed to monitor hearing preservation during surgery.MethodsFor this purpose, Auditory Steady State Responses (ASSRs) were recorded intraoperatively under general anesthesia directly before and after surgical intervention. In contrast to other common electrophysiological methods such as Auditory Brainstem Responses (ABR) or Electrocochleography (ECochG), where transient potentials are measured and evaluated in the time domain for the presence or absence of certain waveforms, with ASSR stationary potentials are measured and evaluated using the phase or frequency of the recorded signal and calculating the probability that a stimulus response is present. ASSR thresholds were recorded at six frequencies (250 Hz, 500 Hz, 1 kHz, 2 kHz, 4 kHz, and 8 kHz) using sine waves. The measurements were completed for 155 ears, with 78 ears being provided with a Nucleus SRA electrode, 55 ears had a Hybrid-L electrode and 22 ears were fitted with other types of electrode.ResultsASSR threshold shifts correlated to hearing threshold shifts modestly but significantly at 1 kHz (r = 0.34, p < 0.01), where the recorded ASSR thresholds were closer to the hearing thresholds than at 250 and 500 Hz and less variance occurred.DiscussionThis suggests that, in many cases, damage to residual hearing is due to intraoperative adverse events, like trauma to the cochlea or mechanical dampening of the basilar membrane. Therefore, ASSR offers certain prospects for the early detection of damage to residual hearing and thus the option for early intervention. ASSR recordings of all frequencies are time consuming. However, based on the data presented here, we would recommend including a reduced measurement protocol, just at 1 kHz, in a future system for monitoring residual hearing during CI insertion complementary to other possible measurement methods. We would also suggest investigating whether the use of chirp stimuli instead of sine waves would lead to higher correlations.